Efficacy of Silver Diamine Fluoride: An Effective Approach for Reducing Hyper Sensitivity in Restorative Dentistry - pervez, Jazib; Bushra Ghani; Memona Ali; Ifrah Zafar; Hafiz Muhammad Adil; Usman Ashraf (Medical Journal of South Punjab, 2024)
Objective: This study aimed to investigate the efficacy of 38% Silver Diamine Fluoride (SDF) in reducing Dentinal Hypersensitivity. Methods: The study involved 90 patients having non-carious cervical lesions or root caries, and reporting hypersensitivity in the affected tooth. Participants were arbitrarily assigned to 2 groups: Group A received 38% SDF treatment, while Group B received 5% Sodium Fluoride NaF varnish. The primary outcome was evaluated by a dental consultant using a compressed air blast to assess dentin hypersensitivity. The data were collected at baseline, immediately after the intervention, and during a follow-up after one month. Results: The results indicated that SDF demonstrated superior efficacy in reducing post-operative sensitivity compared to the NaF varnish group. The effects of SDF were longer-lasting, making it a potential treatment option for dentine hypersensitivity. Conclusion: This study shows that 38% SDF has better efficacy in reducing post-operative sensitivity compared to the NaF varnish group. The effects of SDF were long-lasting, making it a viable treatment for dentine hypersensitivity. This study contributes to the growing interest in SDF usage for various dental applications and emphasizes its potential benefits in managing hyper sensitivity in restorative dentistry.